Enhancing soil health through balanced fertilization: a pathway to sustainable agriculture and food security - Xing, Yingying; Xie, Yunxia; Wang, Xiukang (Frontiers in Microbiology, 2025)
Sustainable soil health management is pivotal for advancing agricultural productivity and ensuring global food security. This review comprehensively evaluates the effects of mineral-organic fertilizer ratios on soil microbial communities, enzymatic dynamics, functional gene abundance, and holistic soil health. By integrating bioinformatics, enzyme activity assays, and metagenomic analyses, we demonstrate that balanced fertilization significantly enhances microbial diversity, community stability, and functional resilience against environmental stressors. Specifically, the synergistic application of mineral and organic fertilizers elevates β-glucosidase and urease activities, accelerating organic matter decomposition and nutrient cycling while modulating microbial taxa critical for nutrient transformation and pathogen suppression. Notably, replacing 20–40% of mineral fertilizers with organic alternatives mitigates environmental risks such as greenhouse gas emissions and nutrient leaching while sustaining crop yields. This dual approach improves soil structure, boosts water and nutrient retention capacity, and increases microbial biomass by 20–30%, fostering long-term soil fertility. Field trials reveal yield increases of 25–40% in crops like rice and maize under combined fertilization, alongside enhanced soil organic carbon (110.6%) and nitrogen content (59.2%). The findings underscore the necessity of adopting region-specific, balanced fertilization strategies to optimize ecological sustainability and agricultural productivity. Future research should prioritize refining fertilization frameworks through interdisciplinary approaches, addressing soil-crop-climate interactions, and scaling these practices to diverse agroecosystems. By aligning agricultural policies with ecological principles, stakeholders can safeguard soil health—a cornerstone of environmental sustainability and human wellbeing—while securing resilient food systems for future generations.